ANALISIS TERHADAP HUBUNGAN ANTARA KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDART (IFRS), MANAJEMEN LABA DAN KUALITAS AUDIT (Studi Empiris pada Industri Properti dan Real Estat yang Terdaftar di Bursa Efek Indonesia Tahun 2007 dan 2013) - Intan Bias Papeke; Endang Kiswara (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the relationship between the convergence of IFRS , earnings management and audit quality. Based on the research of Van Tendeloo and Vanstraelen (2005), proposed that audit quality may be associated between the convergence of IFRS and earnings management . The research was done by executing the financial reporting in 2007( before convergence IFRS) and in 2013 ( after the convergence of IFRS ) at real estate and property companies with a total sample of 34 companies . Analysis tools used include non-parametic Wilcoxon Signed Rank Test, Mann Whitney U test and Sobel test. The results showed that there is differences in earnings management before and after convergence IFRS. In addition, this study reveals that there is no differences in earnings management when the company was audited by big 4 Auditor and non big 4 Auditor. Meanwhile, the results of this study stated that audit quality is not associated between the convergence of IFRS and earnings management.Implication of this research showed that audit quality is not associated with earnings managementand the relationship between the convergence of IFRS and earnings management